Is sCD163 a Clinical Significant Prognostic Value in Cancers? A Systematic Review and Meta-Analysis - Qian, Shushu; Zhang, Hong; Dai, Huibo; Ma, Bangyun; Tian, Fang; Jiang, PengJun; Gao, Haoran; Sha, Xiaocao; Sun, Xuemei (Frontiers in Oncology, 2020)
Background: Tumor associated macrophages (TAMs), a kind of inflammatory cells in the tumor microenvironment, are crucial for the occurrence and development of various tumors which increased the expression of CD163. However, little is known on soluble CD163 and its association with prognosis in tumors. Here we performed a metaanalysis to establish the prognostic significance of serum sCD163 for tumors. Methods: A systematic literature search through June 2020 was performed to evaluate the association between sCD163 and overall survival (OS) or progression-free survival (PFS) in patients with tumors. Data were extracted from studies reporting hazard ratios (HRs) and 95% confidence interval (CI) and pooled using the Mantel-Haenszel random-effect model. Results: Eight studies with a total of 1236 individuals were included in the metaanalysis. Pooled analyses revealed that elevated serum sCD163 was associated with worse OS (HR=2.24, 95% CI: 1.50-3.35, P<0.001) and PFS (HR=3.90, 95% CI: 2.33-6.52, P<0.001) in tumors. Subgroup analysis stratified by medium age at diagnosis demonstrated that patients over 60 years old with high sCD163 had worse OS (HR 2.28, 95% CI: 1.58-3.29, P<0.001) than under 60 (HR 1.43, 95% CI: 1.15-1.77, P=0.001). Subgroup analysis revealed that analysis method and medium age at diagnosis were the potential source of heterogeneity. Conclusions: Overall, high levels of sCD163 could be an adverse prognostic indicator for tumor. Large-scale prospective studies investigating its survival outcomes in cancers are advocated.